Transformasi Sosial Dalam Novel An Enola Holmes Mystery The Case Of The Missing Marquess Karya Nancy Springer - Mutia Lupitasari (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
In this study to analyze how social transformation contained in the novel An Enola Holmes Mystery The Case Of The Missing Marquesss in the Victorian Era. The author used a qualitative descriptive approach in this study. The qualitative descriptive approach refers to the formulation of problems that encourage research to explore or photograph social situations to be researched thoroughly, deeply, and deeply. As a result of this research we can understand the historical and cultural context in the novel, which is set in Victorian era 18th century England. It will provide insight into social, cultural, or historical aspects related to the characters' lives and enrich understanding of their social context. And we can contribute to the study, especially English literature by examining aspects of life transformation in the novel An Enola Holmes Mystery The Case Of The Missing Marquess.